SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN BIJI KOPI BERKUALITAS MENGGUNAKAN (SIMPLE ADDITIVE WEIGHTING) - Kelvin Julian Tannius; Jap Tji Beng; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
The purpose of this paper is to develop a Decision Support System for determining quality coffee beans based on existing criteria. The method used is the Simple Additive Weighting (SAW). The results obtained are Decision Support Systems that can be accessed by Admin and Customer to select the desired coffee beans that are run by using XAMPP as Localhost and PHPMyAdmin as a Database. Based on the experiments conducted, it can be concluded that the system created can be run and can help customers in making decisions to determine quality coffee beans